'once they see blood then the mood for sex is spoiled' A qualitative exploration of female sex worker's male client views of menstruation, sex during menses and the menstrual disc. - Edyth Osire; Sophie Young; Enid Awiti; Cynthia Akinyi; Fredrick Otieno; Penelope A Phillips-Howard; Supriya D Mehta; Linda Mason (PLoS ONE, 2024)
To continue working during menses, female sex workers (FSW) may use unhygienic absorbents to hide their menstrual status. The menstrual disc may provide a solution. Little is known about men's knowledge and views, specifically around sex during menstruation with FSW, a population who are particularly vulnerable to violence which may be heightened during menses. To identify constructs for successful and safe menstrual disc implementation we sought to identify knowledge and attitudes towards menstruation among male clients of FSW, including views on FSW menstrual disc use during intercourse. We conducted six focus group discussions comprising a total of 51 male clients of FSW, in Kisumu, Kenya, exploring their perceptions of menses and sex during menses. In preparation for future implementation of a menstrual disc intervention, we introduced the disc to participants with an information session, answering their questions and gathering their opinions on it. Thematic analysis found most clients had limited or inaccurate knowledge about menstruation, viewing blood and the menstruator, as dirty or unclean. Sources of knowledge included school, female relatives/partners, community or church. Those reporting formal education described the biological processes more accurately, while church education lent towards stigmatized perceptions. Most participants expressed negative views towards sex during menses (i.e., unpleasurable, forbidden or risky), usually stemming from misconceptions, and reported seeking FSW services because their wife / girlfriend was menstruating. Many felt deceived if a FSW was menstruating, were often aware of materials placed vaginally to absorb blood, but generally continued with the service. No clients had prior knowledge of the menstrual disc but accepted it as a safe, hygienic, and cost-effective alternative, with some voicing interest to purchase for their wife / girlfriend. We conclude there is a need to provide accurate information on menstruation to boys and men including in school curricula and faith teaching to address lack of knowledge and negativity. These findings suggest potential for adoption of menstrual discs by FSW with minimal adverse client reaction, and highlight possible partner support for women considering adopting a menstrual disc.